Effective Microorganism (EM) from Modified Bioinoculant to Increase Biogas Quantity - Nurweni, Susi; Karno, Karno; Suyanto, Beny (Health Notions, 2017)
The result of the study can be implemented by, of and for the community, as a renewable energy substitution for LPG easily and in reasonable prize